Communicating the best available science to inform Antarctic policy and management: a practical introduction for researchers - Hughes, Kevin A.; Lowther, Andrew; Gilbert, Neil; Waluda, Claire M.; Lee, Jasmine R. (Antarctic Science, 2023)
Communication at the science-policy interface can be bewildering not only for early-career researchers, but also for many within the research community. In the context of Antarctica and the Southern Ocean, decision-makers operating within the Antarctic Treaty System (ATS) aspire to use the best available science as a basis for their decision-making. Therefore, to maximize the impact of Antarctic Treaty Parties' substantial investment in southern polar research, researchers wishing to contribute to policy and management must understand 1) how their work relates to and can potentially inform Antarctic and/or global policy and 2) the available mechanisms by which their research can be communicated to decision-makers. Recognizing these needs, we describe the main legal instruments relevant to Antarctic governance (primarily the ATS) and the associated meetings and stakeholders that contribute to policy development for the region. We highlight effective mechanisms by which Antarctic researchers may communicate their science into the policy realm, including through National Delegations or the Scientific Committee on Antarctic Research (SCAR), and we detail the key contemporary topics of interest to decision-makers, including those issues where further research is needed. Finally, we describe challenges at the Antarctic science-policy interface that may potentially slow or halt policy development.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forskning; forvaltning; kommunikasjon

The effectiveness of Virkon® S disinfectant against an invasive insect and implications for Antarctic biosecurity practices - Bartlett, Jesamine C; Radcliffe, Richard James; Convey, Pete; Hughes, Kevin A; Hayward, Scott A L (Antarctic Science, 2021)
The flightless midge Eretmoptera murphyi is thought to be continuing its invasion of Signy Island via the treads of personnel boots. Current boot-wash biosecurity protocols in the Antarctic region rely on microbial biocides, primarily Virkon® S. As pesticides have limited approval for use in the Antarctic Treaty area, we investigated the efficacy of Virkon® S in controlling the spread of E. murphyi using boot-wash simulations and maximum threshold exposures. We found that E. murphyi tolerates over 8 h of submergence in 1% Virkon® S. Higher concentrations increased effectiveness, but larvae still exhibited > 50% survival after 5 h in 10% Virkon® S. Salt and hot water treatments (without Virkon® S) were explored as possible alternatives. Salt water proved ineffective, with mortality only in first-instar larvae across multi-day exposures. Larvae experienced 100% mortality when exposed for 10 s to 50°C water, but they showed complete survival at 45°C. Given that current boot-wash protocols alone are an ineffective control of this invasive insect, we advocate hot water (> 50°C) to remove soil, followed by Virkon® S as a microbial biocide on ‘clean’ boots. Implications for the spread of invasive invertebrates as a result of increased human activity in the Antarctic region are discussed.
Keywords: Antarktis; biologi; biosikkerhet; fjærmygg; forurensning; klimaendringer; miljøpåvirkning; økologi; økosystemer

Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation’: a new SCAR Scientific Research Programme - Hughes, Kevin A.; Santos, Mercedes; Caccavo, Jilda A.; Chignell, Stephen M.; Gardiner, Natasha B.; Gilbert, Neil; Howkins, Adrian; Van Vuuren, Bettine Jansen; Lee, Jasmine R.; Liggett, Daniela; Lowther, Andrew; Lynch, Heather; et al. (Antarctic Science, 2022)
Antarctic and Southern Ocean environments are facing increasing pressure from multiple threats. The Antarctic Treaty System regularly looks to the Scientific Committee on Antarctic Research (SCAR) for the provision of independent and objective advice based on the best available science to support decision-making, policy development and effective environmental management. The recently approved SCAR Scientific Research Programme Ant-ICON - ‘Integrated Science to Inform Antarctic and Southern Ocean Conservation‘ - facilitates and coordinates high-quality transdisciplinary research to inform the conservation and management of Antarctica, the Southern Ocean and the sub-Antarctic in the context of current and future impacts. The work of Ant-ICON focuses on three research themes examining 1) the current state and future projections of Antarctic systems, species and functions, 2) human impacts and sustainability and 3) socio-ecological approaches to Antarctic and Southern Ocean conservation, and one synthesis theme that seeks to facilitate the provision of timely scientific advice to support effective Antarctic conservation. Research outputs will address the most pressing environmental challenges facing Antarctica and offer high-quality science to policy and advisory bodies including the Antarctic Treaty Consultative Meeting, the Committee for Environmental Protection and the Scientific Committee of the Commission for the Conservation of Antarctic Marine Living Resources.
Keywords: Antarktis; Antarktistraktaten; Sørishavet; forvaltning; human impact; miljøvern

TerrANTALife 1.0 Biodiversity data checklist of known Antarctic terrestrial and freshwater life forms - Pertierra, Luis R.; Varliero, Gilda; Barbosa, Andrés; Biersma, Elisabeth M.; Convey, Peter; Chown, Steven L.; Cowan, Don; De Los Rios, Asunción; Escribano-Alvarez, Pablo; Fontaneto, Diego; Fraser, Ceridwen; Harris, Mathew; et al. (Biodiversity Data Journal, 2024)
Incomplete species inventories for Antarctica represent a key challenge for comprehensive ecological research and conservation in the region. Additionally, data required to understand population dynamics, rates of evolution, spatial ranges, functional traits, physiological tolerances and species interactions, all of which are fundamental to disentangle the different functional elements of Antarctic biodiversity, are mostly missing. However, much of the fauna, flora and microbiota in the emerged ice-free land of the continent have an uncertain presence and/or unresolved status, with entire biodiversity compendia of prokaryotic groups (e.g. bacteria) being missing. All the available biodiversity information requires consolidation, cross-validation, re-assessment and steady systematic inclusion in order to create a robust catalogue of biodiversity for the continent.We compiled, completed and revised eukaryotic species inventories present in terrestrial and freshwater ecosystems in Antarctica in a new living database: terrANTALife (version 1.0). The database includes the first integration in a compendium for many groups of eukaryotic microorganisms. We also introduce a first catalogue of amplicon sequence variants (ASVs) of prokaryotic biodiversity. Available compendia and literature to date were searched for Antarctic terrestrial and freshwater species, integrated, taxonomically harmonised and curated by experts to create comprehensive checklists of Antarctic organisms. The final inventories comprises 470 animal species (including vertebrates, free-living invertebrates and parasites), 306 plants (including all Viridiplantae: embryophytes and green algae), 997 fungal species and 434 protists (sensu lato). We also provide a first account for many groups of microorganisms, including non-lichenised fungi and multiple groups of eukaryotic unicellular species (Stramenophila, Alveolata and Rhizaria (SAR), Chromists and Amoeba), jointly referred to as "protists". In addition, we identify 1753 bacterial (obtained from 348117 ASVs) and 34 archaeal genera (from 1848 ASVs), as well as, at least, 14 virus families. We formulate a basic tree of life in Antarctica with the main lineages listed in the region and their “known-accepted-species” numbers.
Keywords: Antarktis; Sørishavet; biodiversitet; database; fauna; flora; mikroorganismer

Threat management priorities for conserving Antarctic biodiversity - Lee, Jasmine R.; Terauds, Aleks; Carwardine, Josie; Shaw, Justine D.; Fuller, Richard A.; Possingham, Hugh P.; Chown, Steven L.; Convey, Peter; Gilbert, Neil; Hughes, Kevin A.; McIvor, Ewan; Robinson, Sharon A.; et al. (PLOS Biology, 2022)
Antarctic terrestrial biodiversity faces multiple threats, from invasive species to climate change. Yet no large-scale assessments of threat management strategies exist. Applying a structured participatory approach, we demonstrate that existing conservation efforts are insufficient in a changing world, estimating that 65% (at best 37%, at worst 97%) of native terrestrial taxa and land-associated seabirds are likely to decline by 2100 under current trajectories. Emperor penguins are identified as the most vulnerable taxon, followed by other seabirds and dry soil nematodes. We find that implementing 10 key threat management strategies in parallel, at an estimated present-day equivalent annual cost of US$23 million, could benefit up to 84% of Antarctic taxa. Climate change is identified as the most pervasive threat to Antarctic biodiversity and influencing global policy to effectively limit climate change is the most beneficial conservation strategy. However, minimising impacts of human activities and improved planning and management of new infrastructure projects are cost-effective and will help to minimise regional threats. Simultaneous global and regional efforts are critical to secure Antarctic biodiversity for future generations.
Keywords: Antarktis; biodiversitet; forvaltning; pingviner